Citizen responsive government - Hoggart, Keith; Clark, Terry N. (New York : JAI, 2000)
How can government stay linked to its citizens? Across the world, governments' basic principles are turned on their heads as global markets, weakened national states, and active citizens emerge. Governments increasingly act not alone, but many governments and private groups make policy jointly - labeled 'governance'. But this raises new concerns for adequate citizen responsiveness. Leaders and parties previously considered left or right make unexpected choices - as leaders explore Third Ways, New Political Cultures, and more. As policy choices grow more complicated, they are harder to present to citizens - which undermines citizen legitimacy of parties and elected officials. How can government maintain democratic accountability? This volume explores new answers by probing citizen involvement in specific cities and countries the world over. There is no single problem, hence no single remedy. But by contrasting key elements of national and local contexts, this volume offers lessons about how citizens are variously activated; about what works, where, and why. From specific results emerge insights about how citizens may drive policy, or be ignored, in a time of turbulence and rapid cultural change for government policy making.
Includes bibliographical references.
Description based on print version record.
Keywords: Municipal government; Political participation; Central government policies; Urban & municipal planning; Political Science -- Public Policy -- City Planning & Urban Development